Coronary Microvascular Dysfunction: Insights on Prognosis and Future Perspectives - Filippo Luca Gurgoglione; Giorgio Benatti; Andrea Denegri; Davide Donelli; Marco Covani; Mattia De Gregorio; Gabriella Dallaglio; Rebecca Navacchi; Giampaolo Niccoli (Reviews in Cardiovascular Medicine)
Coronary microvascular dysfunction (CMD) comprises a wide spectrum of structural and/or functional abnormalities of coronary microcirculation that can lead to myocardial ischemia. Emerging evidence has indicated that CMD is a relevant cause of morbidity and mortality and is associated with a high risk of major adverse cardiovascular events (MACEs) and heart failure with preserved ejection fraction as well as poor quality of life. This review aims to elucidate briefly the pathogenesis and diagnostic modalities of CMD and to shed light on contemporary evidence on the prognostic impact of CMD. Finally, we will provide an overview of novel emerging therapeutic strategies for CMD.